Factors effecting the success of Bumiputre franchisees in business - Baputey, Sulaiman (1998)
This study explored factors that contribute to the success of Bumiputra franchisees and factors that make other Bumiputra franchisees less successful in similar industry. Using a mail survey, data were collected from sixty Bumiputra franchisees from the list provided by Ministry of Entrepreneur Development. Simple random sampling was applied to select the respondents before sending them questionnaire. Perceptional questions were used to differentiate between Bumiputra franchisees who perceived themselves as successful and Bumiputra franchisees who perceived themselves to be less successful. The franchisor congenial relations was found to be stronger factor affecting the success of Bumiputra franchisees. This factor was again elaborated in terms of having good rapport with franchisor, training and development provided by the franchisor and cooperation from the franchisor.